Implementasi Strategi Pemasaran Online Berbasis Platform E-Peken pada UMKM di Kecamatan Wiyung Surabaya - Kinanti, Anggreini Ratna; Dwiridotjahjono, Jojok (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Surabaya City Department of Cooperatives and Small Business Trade (Dinkopdag) plays an important role in efforts to strengthen MSMEs, especially grocery stores. The Surabaya City Dinkopdag has launched various programs and initiatives to support the growth and sustainability of grocery stores. These programs include entrepreneurship training, facilitating access to capital, as well as marketing assistance including the use of the e-peken platform and product promotion. These initiatives not only aim to increase business capacity but also increase business competitiveness.This paper aims to describe the implementation of an online marketing strategy based on the e-peken platform in MSMEs (especially grocery stores) in Wiyung District, Surabaya. The e-peken platform will help increase efficiency and effectiveness in business management. Online Marketing Strategy: through the e-peken platform/application it will help and reach more customers so that it can make a positive contribution to marketing performance and increase business capacity.